2005
DOI: 10.1200/jco.2005.12.187
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Randomized Phase II Study of Two Schedules of Docetaxel, Estramustine, and Prednisone Versus Mitoxantrone Plus Prednisone in Patients With Metastatic Hormone-Refractory Prostate Cancer

Abstract: The results of this randomized phase II study showed significantly higher PSA decline < or = 50% and longer times to progression in HRPC patients receiving DEP-based chemotherapy than MP, and that DEP could be proposed in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
1
6

Year Published

2006
2006
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(92 citation statements)
references
References 24 publications
6
79
1
6
Order By: Relevance
“…The serum PSA was thought to be correlated with cancer emergence, progression and efficacy of treatment [14,15], and some scholars proclaimed that the 'PSA era' had begun. However, many studies have found that serum PSA as an end point was unstable and heterogeneous for evaluating prognoses [16][17][18]. To improve the value of prediction, kinetic parameters based on PSA were developed that could more precisely reflect biological characteristics [7,13,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The serum PSA was thought to be correlated with cancer emergence, progression and efficacy of treatment [14,15], and some scholars proclaimed that the 'PSA era' had begun. However, many studies have found that serum PSA as an end point was unstable and heterogeneous for evaluating prognoses [16][17][18]. To improve the value of prediction, kinetic parameters based on PSA were developed that could more precisely reflect biological characteristics [7,13,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the taxanes (paclitaxel or docetaxel) with other agents, such as EMP or predonisone have been used for hormone-resistant prostate cancer (HRPC) and have shown good response (2)(3)(4)(5). Paclitaxel, which is purified from Taxus brevifolia, stabilize microtubule and causes apoptosis (6).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, besides vinorelbine, 22,23 several studies have combined a taxane with estramustine with encouraging results in terms of response rate and survival. [24][25][26][27] However, significant toxicity was again observed in all of these studies. The thrombotic complications have been a source of concern for many investigators and have resulted in prophylactic regimens being introduced into the trials, with the aim of mitigating this toxicity.…”
Section: Discussionmentioning
confidence: 85%